2013
DOI: 10.5543/tkda.2013.15146
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of alternative herbal medicine and nutritional complementary product intake in patients admitted to out-patient cardiology departments

Abstract: Alternative and complementary products were common in patients admitted to outpatient cardiology clinics. Female gender, advanced age, higher education level, drug intake, and having a chronic illness were predisposing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…In contrast to the studies [ 3 , 4 , 7 ], we did not find a relationship between herbal medicine use and education level. Previous studies found that people who had high education level were more likely to use herbal medicines.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the studies [ 3 , 4 , 7 ], we did not find a relationship between herbal medicine use and education level. Previous studies found that people who had high education level were more likely to use herbal medicines.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we found that herbal medicines were merely recommended by professional health care providers (7.9% by physicians, 3.2% by pharmacists). Family and friends or media were the main sources of information as seen in previous studies [ 4 , 7 , 11 , 17 ]. This is another important point, which could lead to negative outcomes in the treatment.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations